Interpretation of the Prohibition on Non-Muslim Leaders in the Qur’an (Fazlurrahman's Hermeneutical Perspective) - Adam Wildan Sholeh; Moch. Farich Alfani (al-Afkar, Journal For Islamic Studies, 2026)
The problem of non-Muslim leaders reaps many differences of opinion between figures and each other, they have strong arguments with each other to justify their arguments. One of those who contributed to this conversation was Prof. H. Nadirsyah Hosen, Ph.D or often called gus Nadir. He created a book with the title "Tafsir Al-Qur'an di Medsos" as a response to the problem of actual interpretation today which is only textual. Researchers correlate gus Nadir's interpretation using Fazlurrahman's hermeneutic perspective. This research is library research with a qualitative approach, primary data sources are focused on the book Tafsir Al-Quran in Medsos. The author uses data collection techniques through documentation techniques such as searching, browsing, downloading and screenshots. The question in this study is what is the meaning of the verse prohibiting the choice of non-muslim leaders in his book Gus Nadir when viewed based on Fazlurrahman's hermeneutic glasses? The results of this study found that Gus Nadir allowed the appointment of non-Muslim leaders and the interpretation carried out by him in accordance with the steps of the hermeneutic interpretation of the double movement by Fazlurrahman.